Effects of silica/carbon black hybrid nanoparticles on the dynamic modulus of uncrosslinked cis-1, 4-polyisoprene rubber: Coarse-grained molecular dynamics. (3rd January 2022) - Yuan, Bin; Zeng, Fanlin; Peng, Chao; Wang, Youshan
Abstract: Coarse-grained molecular dynamics (CGMD) simulations are employed to study the viscoelastic properties of cis -1, 4-polyisoprene with silica/carbon black (CB) hybrid nanoparticles (NPs). Our simulation work for the first time investigates the rubber with both silica and CB NPs with the potential functions from the iterative Boltzmann inversion (IBI) method. We calculate the dynamic shear modulus of different models, and analyze the effect of silica/CB ratio and grafted NPs. In order to explain the differences in modulus from the microscopic view, we make the quantitative comparisons of the NP-NP, polymer-polymer and NP-polymer structures, such as using the radius of gyration, the coordination number, and the potential energy. The characteristics of dual phase filler are mainly in two aspects of potential functions. One is that the silica-CB interaction is weaker than that of their single components, and the other is that the NP-polymer potential functions are different in shape for Silica and CB. The former causes NPs to be more likely to aggregate in the form of "bridging". The latter causes that the silica-polymer interaction is weaker at small amplitudes, while the CB-polymer interaction is weaker at large amplitudes for the range of the strong CB-polymer interaction is narrow. The simulation result also shows that the break-up of the NP network is the main factor for the Payne effect, and the interfacial separation is the second factor. The reason why the storage modulus curves of the models with grafted NPs decrease slowly at small amplitudes is the hindering effect of the graft chains on the growth of the interfacial voids. Graphical abstract: Image 1 Highlights: Derivation of the new potential functions from the iterative Boltzmann inversion method. Analysis of the difference in dynamic modulus caused by the potential functions of silica and carbon black. Comparison of the contribution of nanoparticle network, polymer network and nanoparticle-polymer interface to Payne effect.